Evaluation of fuel ethanol production from aqueous ammonia-treated rice straw via simultaneous saccharification and fermentation. (October 2016) - Phitsuwan, Paripok; Permsriburasuk, Chutidet; Waeonukul, Rattiya; Pason, Patthra; Tachaapaikoon, Chakrit; Ratanakhanokchai, Khanok
Abstract: Rice straw (RS) has been considered a promising feedstock for ethanol production in Asia. However, the recalcitrance of biomass, particularly the presence of lignin, hinders the enzymatic saccharification of polysaccharides in RS and consequently decreases the ethanol yield. Here, we used aqueous ammonia pretreatment to remove lignin from RS (aRS). The reaction conditions were a solid:liquid ratio of 1:12, an ammonia concentration of 27% (w w −1 ), room temperature, and a 2-week incubation. We evaluated enzymatic digestibility and the ethanol production yield. A 42% reduction in lignin content increased the glucan conversion of aRS to glucose from 20 to 71% using a combination of Cellic Ctec2 cellulases and Cellic Htec2 xylanases at enzyme loads of 15 FPU +100 XU g −1 solid. Scanning electron microscopy highlighted the extensive removal of external fibres and increased porosity of aRS, which aided the accessibility of cellulose for enzymes. Using the same enzyme dosage and a solid load of 100 g L −1, simultaneous saccharification and fermentation using a monoculture of Saccharomyces cerevisiae and co-culture with Candida tropicalis yielded ethanol concentrations of 22 and 25 g L −1, corresponding to fermentation efficiencies of 96 and 86% fermentation, respectively. The volumetric ethanol productivities for these systems were 0.45 and 0.52 g L −1  h −1 . However, the ethanol yield based on the theoretical glucose and xylose concentrations was lower for the co-culture (0.44 g g −1 ) than the monoculture (0.49 g g −1 ) due to the low xylose consumption. Further research should optimise fermentation variables or select/improve microbial strains capable of fermenting xylose to increase the overall ethanol production yield. Graphical abstract: Highlights: Rice straw was treated with 27% (w w −1 ) aqueous ammonia at room temperature. Lignin was removed by 42%, with exposure of internal fibres. The highest glucan-to-glucose conversion was 71% using a combination of cellulase and xylanase. Ethanol yields were achieved at 96 and 86% for mono- and co-cultures.